Marian Dygo. Mulier fortis. Studia nad Prologiem w „Vita Dorotheae Montoviensis” Jana z Kwidzyna [Mulier Fortis. Studies on the Prologue in „Vita Dorotheae Montoviensis” by Johann Marienwerder].: Warszawa: Wydawnictwo DiG, 2023. 284 pp. ISBN 978-83-286-0222-9. - Biskup, Radosław (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)